(untitled) (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
Schools of legal positivism has been associated with the development of law in Indonesia, namely the creation of the sort order for the legislation set out in the Decree of the People’s Consultative Assembly (MPR) as well as regulated in Law No. 10 of 2004 which refers to the Stufenbau Theory. Besides, the schools also lead to the formation of the Constitutional Court as an institution that serves as the guardian of the constitution.